2011
DOI: 10.1002/aic.12357
|View full text |Cite
|
Sign up to set email alerts
|

Modeling solid–liquid equilibrium of NH4Cl‐MgCl2‐H2O system and its application to recovery of NH4Cl in MgO production

Abstract: A new method to recover NH 4 Cl from NH 4 Cl-rich aqueous solutions generated in the magnesia (MgO) production is developed on the basis of modeling the solid-liquid equilibrium (SLE) for the NH 4 Cl-MgCl 2 -H 2 O system with the Pitzer model embedded in Aspen Plus TM platform. The SLE values for the ternary system were determined from 278.15 to 348.15 K. The new standard-state chemical potentials of NH 4 Cl and MgCl 2 Á6H 2 O were judicially obtained. The resulting equilibrium constants were used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 30 publications
(46 reference statements)
0
27
1
Order By: Relevance
“…The accuracy of Pitzer model in prediction of SLE in NH 4 ClMgCl 2 -H 2 O system has been illustrated in our previous work 6 and is not demonstrated again in the present work. A comparison of experimental data 26,27 with the prediction from the Pitzer model embedded in Aspen Plus TM platform by use of parameters taken from Ji et al 16 is shown in Figure 1 for the SLE in the NH 4 27 It is shown that the solubilities of NH 4 Cl increase with increasing temperature both in NH 4 Cl-NaCl-H 2 O and NH 4 Cl-MgCl 2 -H 2 O systems.…”
Section: Methodscontrasting
confidence: 57%
See 2 more Smart Citations
“…The accuracy of Pitzer model in prediction of SLE in NH 4 ClMgCl 2 -H 2 O system has been illustrated in our previous work 6 and is not demonstrated again in the present work. A comparison of experimental data 26,27 with the prediction from the Pitzer model embedded in Aspen Plus TM platform by use of parameters taken from Ji et al 16 is shown in Figure 1 for the SLE in the NH 4 27 It is shown that the solubilities of NH 4 Cl increase with increasing temperature both in NH 4 Cl-NaCl-H 2 O and NH 4 Cl-MgCl 2 -H 2 O systems.…”
Section: Methodscontrasting
confidence: 57%
“…4 Cl in the soda process, the recovery of NH 4 Cl in MgO production process is also composed by the two consecutive cooling and salting-out operations. 6 In the case of cooling crystallization, as shown in Figure 14, the crystal growth rate increases with increasing concentration of MgCl 2 at the same supersaturation of Dm NH 4 in solution. Further, the increment is gradually magnified as increasing concentration of MgCl 2 , suggesting that the presence of MgCl 2 facilitates the growth of NH 4 Cl.…”
Section: à5mentioning
confidence: 93%
See 1 more Smart Citation
“…[7] China is also rich in saline brine resources that include considerable amounts of mainly Mg. [8] Therefore, enhancing current understanding on the effect of Mg resources on P recovery and crystal quality from urine is essential to improve P recovery from waste. Struvite crystallization does not only require a high PO 3− 4 -P removal efficiency but also a high product quality (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated results were quite consistent with the experimental values with an overall average relative deviation (ARD) of 2.55%. For the binary NH 4 Cl-H 2 O and MgCl 2 -H 2 O systems, the model's prediction based on OLI parameters and the experimental data taken from literature 30,31 were compared over the temperature range from 0 C to 100 C. As shown in Figure 3b, the existing model again gave a good result for the solubility of NH 4 29 Regardless, the recalcualted results were in good agreement with the experimental values as shown in Figure 5 (solid line). Thus, it was confirmed that the new set of MSE model parameters are better at calculating phase equilibria of ternary and quaternary systems involving NH 4 Cl and MgCl 2 .…”
Section: Calculation Of New Mse Parameters For Thermodynamic Modelmentioning
confidence: 99%